Clinical features of anemia in membranous nephropathy patients: a Chinese cohort study - Zhe Li; Weibo Le; Haitao Zhang; Dacheng Chen; Wencui Chen; Shuhua Zhu; Ke Zuo (Renal Failure)
Background Anemia is a common complication in patients with progressive chronic kidney disease. This cohort study evaluated the prevalence, clinical features and prognosis of membranous nephropathy (MN) with anemia.Methods We retrospectively analyzed a cohort of MN patients diagnosed using renal biopsy between February 2012 and February 2018. The clinical and pathological characteristics at baseline were recorded, and the outcomes (hemoglobin, proteinuria and renal function) during follow-ups were also evaluated. Univariate and multivariate logistic regression analyses were performed to identify the independent risk factors for anemia in MN patients. The MN patients were divided according to the therapeutic effect they experienced as follows: without-anemia, completely corrected anemia, standard anemia treatment and nonstandard anemia treatment groups. We compared the rate of complete remission of MN and renal end-point events among the four groups.Results The median age of 483 patients was 42.43 (26.59, 50.20) years at the time of MN diagnosis. The prevalence of anemia at baseline was 23.81%, and the cumulative prevalence was 50.72%. There were 133 cases of mild anemia, 103 cases of moderate anemia and 9 cases of severe anemia; in addition, there were 228 cases of normocytic anemia and 17 cases of microcytic hypochromic anemia. Multivariate logistic regression indicated that acute renal tubule injury >5% (OR = 1.634, 95% CI 1.034, 2.581; p = 0.035), total protein level (OR = 0.949, 95% CI 0.923, 0.975; p < 0.001), cholesterol level (OR = 0.833, 95% CI 0.749, 0.926, p = 0.001), hypokalemia (OR = 2.612, 95% CI 1.227, 5.560, p = 0.013) and hypophosphatemia (OR = 2.653, 95% CI 1.303, 5.403, p = 0.007) were independent risk factors for anemia in MN patients. The complete remission rate of MN patients without anemia was significantly higher than that of anemia patients who exhibited treatment failure. The incidence of renal endpoint events was different among the four groups.Conclusion The anemia experienced by MN patients is mainly mild and moderate, normocytic anemia. The pathological features of acute renal tubular injury and clinical nutritional status are independent risk factors for anemia. There were differences in renal prognosis among anemia patients with different treatment outcomes.